2021
DOI: 10.1097/md.0000000000026569
|View full text |Cite
|
Sign up to set email alerts
|

Time-saving effects using helicopter transportation: comparison to a ground transportation time predicted using a social navigation software

Abstract: BackgroundPrevious comparison studies regarding two types of transportation, helicopter (HEMS) versus ground emergency medical services (GEMS), have shown underlying heterogeneity as these options have completely different routes and consequent times with reference to one patient. To compare the two types of transportation on a case-by-case basis, we analyzed the retrospectively reviewed HEMS and predicted GEMS data using an open-source navigation software. MethodsPatients transferred by military HEMS from 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…HEMS is typically regarded as a better mode of transportation because of its reduced travel time and low risk of unexpected delays. One study demonstrated that HEMS transport saved 56 min when compared to ground medical transport services [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEMS is typically regarded as a better mode of transportation because of its reduced travel time and low risk of unexpected delays. One study demonstrated that HEMS transport saved 56 min when compared to ground medical transport services [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a number of significant advancements in handling these combat-related emergencies, which have improved the survival of severely injured individuals, there is always a need to further reduce the elapsed time from trauma to optimal treatment or to provide better on-site immediate care. Although the duration of the 'golden hour' does not always correlate with morbidity or mortality [82], the early transport of injured individuals to fully equipped medical facilities via helicopter emergency medical service (EMS), or another means, often improves survival [83]. At a minimum, for the severely injured combatant, it is psychologically reassuring to undergo treatment in an intensive care hospital setting as opposed to on the battlefield.…”
Section: Extending the 'Golden Hour' To Improve Medical Outcomesmentioning
confidence: 99%
“… 2 Since the 1960s, helicopters have been integrated into EMS systems to cover remote areas 3 and shorten transport times. 4 , 5 , 6 They provide specialized medical personnel and equipment to the emergency scene and are crucial for maintaining a high standard of care. 3 , 7 In Europe, Luxembourg, Switzerland and Austria are the countries with the highest density of rescue helicopters per population and area.…”
Section: Introductionmentioning
confidence: 99%